2015
DOI: 10.1007/s12161-015-0102-1
|View full text |Cite
|
Sign up to set email alerts
|

pH and CO2 Sensing by Curcumin-Coloured Cellophane Test Strip

Abstract: 2 pH and CO 2 sensing by curcumin coloured cellophane test strip ABSTRACTCurcumin coloured cellophane test strip -fabricated without any synthetic material -is used to determine in situ the instantaneous pH changes in liquids and in the air. A low cost, portable sensor array for possible medical and food-industrial application is developed. Next to the pH detection, curcumin coloured test strip can be applied as CO 2 monitoring sensor, too. On-going processes and the structural changes are followed by UV-VIS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Based on previous results curcumin-coloured (Pávai et al 2015a) cellophane strips (Pávai et al 2015b) are well applicable for pH and CO 2 sensing.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Based on previous results curcumin-coloured (Pávai et al 2015a) cellophane strips (Pávai et al 2015b) are well applicable for pH and CO 2 sensing.…”
Section: Introductionmentioning
confidence: 62%
“…The novelties of the sensitive (comparing to the bare eye checking) smartphone camera based method (comparing to the test strips presented in our previous paper (Pávai et al 2015a)) are the real time monitoring option of the pH changes; development a new type of curcumindotted cellophane test strip, that allows multiple sample analyses simultaneously; the preparation of long time stable curcumin-coloured gelatine capsules, applicable more easier at cattering, mobile vendors or households. Schematic illustration of colour determination by the camera of the smartphone is presented on Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these synthetic chemical dyes may contaminate the food and pose a threat to human health owing to their potential toxicity [ 18 ]. Recently, several studies have reported the potential use of natural pH-sensing dyes such as curcumin and anthocyanin, which are extracted from plants, in intelligent food packaging films [ 2 , 12 , 19 , 20 ]. Natural dyes have more obvious advantages, including nontoxicity, easy preparation, renewability, and a non-polluting nature [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods require expensive equipment, professional operators, and long processing time. Lateral flow immunoassay (LFA) is a screening method used for on-site testing owing to its advantages of convenience (Pávai, Mihály, & Paszternák, 2015;Wu, Liu, et al, 2016), sensitivity, and speed. Colloidal gold (CG) nanoparticles are the most commonly used labeling materials to detect various analytes (Lai, Fung, Yang, Renrong, & Xiong, 2009;Wu, Guo, Dong, & Song, 2016).…”
Section: Introductionmentioning
confidence: 99%